Modeling a Sustainable, Self-Energized Pine Dust Pyrolysis System With Staged Condensation for Optimal Recovery of Bio-Oil - Charis, Gratitude; Danha, Gwiranai; Muzenda, Edison; Nhubu, Trust (Frontiers in Energy Research, 2021)
This simulation study explores sustainable improvements that could be made to a pine dust pyrolysis system to eliminate total dependence on external electrical energy supply and improve the yield of high-quality dry bio-oil. The components, stoichiometric yield and composition of oil, char and gas were modeled in ChemCAD using data from literature and results from biomass characterization and pyrolysis. A fast pyrolysis regime was used to increase the overall yield of dry oil fraction recovered and the char by-product was utilized to make the system energy self-sufficient. The optimization study focused on the condensation system whose parameters were varied at the provided optimum pyrolysis temperature. The recommended temperature for the primary condenser was 96–110°C which yielded 23.3–29.8 wt% dry oil with 2.4–4.4 wt% water content. The optimum temperature for the secondary condenser was 82°C whose bio-oil (∼2.92 wt%) had a moisture content of 7.5–10 wt% at constant primary condenser temperature between 96–110°C. The third condenser could be operated at ambient temperature. The results were validated using both information reported in literature and results from the previous experimental study. Such a simple model built by careful selection of the model bio-oil components is useful in estimating the optimal parameters for the biomass pyrolysis staged condensation system.